The Sclera - Sainz de la Maza, Maite; Tauber, Joseph; Foster, C. Stephen; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
The Sclera is the definitive text on the diagnosis and treatment of scleral diseases, with in-depth chapters on non-infectious scleritis, infectious sclertitis, non-inflammatory diseases of the sclera, and systemic implications of scleral disease. Basic physiology, anatomy, and biochemistry are addressed as well. Written for the ophthalmologist, the revised and updated new edition of The Sclera contains the most current information available on newer characterizations of the composition of the sclera, immune derangements of it, and success in medical and surgical treatment of the inflammatory diseases of the sclera.
1. Structural Considerations of the Sclera -- 2. Immunologic Considerations of the Sclera -- 3. Diagnostic Approach to Episcleritis and Scleritis -- 4. Clinical Considerations of the Episcleritis and Scleritis -- 5. Pathology in Scleritis -- 6. Non Infectious Scleritis -- 7. Infectious Scleritis -- 8. Non Inflammatory Diseases of the Sclera -- 9. Treatment of Episcleritis and Scleritis.
Keywords: Medicine; Family medicine; Ophthalmology; Medicine & Public Health; Ophthalmology; General Practice / Family Medicine